KESENJANGAN INVESTASI DAN EVALUASI KEBIJAKAN PEMEKARAN WILAYAH DI INDONESIA - Yuliadi, Imamudin (Universitas Muhammdaiyah Surakarta, 2012)
The development of local participation and economic potential is the aim of the policy of regional autonomy through regional expansion. The policy of regional expansion also brings new problems such as the problem of economic and bureaucratic burden that must be borne by the government and local communities. This study used some formulas to describe the objects of the research that has been established regarding the economic potential of the region, SMEs and entrepreneurship, investment gap and fiscal gap. To explain the policy implications of the expansion of the region to economic justice, then the economic analysis in this research comes with regional economic and investment disparities study. The object of this study is the province of Gorontalo which is a result of the policy of regional expansion. This research is a descriptive-analytic because in addition to get an overview of each condition variable such research, as well as to know the relation between the variables in the study.